Kastolan Theory Error Analysis on Vocational School Students – A Case on Sequences and Series Topics - Nurhasanah, Alya Siti; Anita, Ika Wahyu (IKIP Siliwangi, 2025)
The purpose of this study is to analyze the mistakes made by students while working on math problems in Sequence and series. The background to this study is that it is difficult to understand students during their studies, which leads to mistakes in solving the math problems of Sequence and series. The purpose of this study is to determine what mistakes are common in solving questions about Sequence and series. The subjects of this study were 10 students of eleventh grade at SMK Plus Darussurur, Cimahi City. The data collection method uses written essay questions with results obtained from the analysis of the level of error based on the Kastolan Theory. Based on the results of the research and discussion, it was found that the level of student errors in working on sequence and series problems is as follows : 1) Conceptual errors with a percentage rate of 50% with the criterion of